SOCIAL EXPECTATIONS AND LIFE VALUES OF STUDENTS UNDER VARIOUS CONDITIONS OF THEIR EDUCATION AT A MEDICAL UNIVERSITY - Мария Михайловна Стульба; Эдгар Артурович Мордовский; Владимир Александрович Плаксин; Андрей Геннадьевич Лукашов (Medicina v Kuzbasse, 2023)
Against the background of an increase in the control figures of admission of applicants to medical universities, the problem of low readiness of the majority of students to work in their future specialty remains urgent. The purpose of the study is to assess the social expectations and value orientations of medical university students associated with their willingness to work in their specialty. Materials and methods. A cross-sectional sociological study was carried out by means of a questionnaire survey of 245 students of 1-6 courses in the specialty programs of the Northern State Medical University (Arkhangelsk). The author's questionnaire was used; it included the questionnaire Brown D., Crace RK. Crace «Assessment of values that determine behavior and decision-making» (Life Values Inventory). Results. Contract students demonstrate the highest willingness to work in their chosen specialty; every tenth student on a budget basis (12.2 %) and under a target contract (11.5 %) doubted the choice of profession (p (Pearson's test χ2) = 0.012). Regardless of the conditions of education for the future physicians, the most important are: the possibility of professional growth, further professional development, professional results with an increase in income. In the group of students on a budget basis and according to a target agreement, the least expressed value orientations are «spirituality», «humility», «creativity» and «belonging»; and the most pronounced are «privacy», «responsibility» and «financial prosperity». In the group of contract students, almost all dimensions of value orientations were expressed to a significant extent. Conclusion. The obtained results can be used in the development of measures aimed at improving the readiness of medical university students for future professional activity.